1978
DOI: 10.1007/bf01966613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fenclofenac on prostaglandin production in carageenin air bleb exudates in rats

Abstract: Employing a modified carrageenin air bleb technique in rats, the effect was studied of fenclofenac and standard drugs (acetylsalicylic acid, indomethacin and phenylbutazone) on prostaglandin production in inflammatory exudate. In common with the standard drugs, fenclofenac reduced exudate prostaglandin levels, being approximately equipotent with phenylbutazone in this respect. Also, an attempt was made to relate the effect of fenclofenac and standard drugs on prostaglandins to their acute anti-inflammatory act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…As mentioned before, fenclofenac [a close analogue of fcnoprofen (Lilly)], first thought to be of the classical type (49) has now been found to modulate the immune system (43). Again in animal studies, this product was found to have minimal activity in the acute but strong activity in the chronic assays.…”
Section: This Mode Of Action Might Reflect Selective Stimulation Of Bmentioning
confidence: 99%
“…As mentioned before, fenclofenac [a close analogue of fcnoprofen (Lilly)], first thought to be of the classical type (49) has now been found to modulate the immune system (43). Again in animal studies, this product was found to have minimal activity in the acute but strong activity in the chronic assays.…”
Section: This Mode Of Action Might Reflect Selective Stimulation Of Bmentioning
confidence: 99%
“…These apparent qualitative similarities have no doubt contributed to the wide acceptance of the unifying hypothesis that the biological activities of these agents result from their common ability to inhibit prostaglandin biosynthesis [1][2][3]. Whilst this hypothesis has been seriously questioned from several quarters [4][5][6], it is still generally believed that their activities result from the same combination of mechanisms, if not solely from their effects on prostaglandins. Thus, by extrapolation, it might be expected that, in terms of clinical efficacy (as opposed to potency), none of these NSAAIAs is likely to have any significant advantage over any other in the same class, all having merely a palliative action in rheumatic diseases.…”
mentioning
confidence: 98%
“…Evidence accumulated over the last decade has led to a hypothesis that their mode of action resides in the ability of the drugs to inhibit the production of biologically active lipids from arachidonic acid by inhibiting prostaglandin cyclooxygenase (Ferreira & Vane 1979;Vane 1978). Whilst this effect is not disputed, there is now available a substantial literature which would argue that other antiinflammatory actions of these drugs, particularly those directed against leucocyte accumulation in inflammatory exudates, are unrelated to their effects on prostaglandin cyclo-oxygenase (Walker et al 1976;Glenn et a1 1977;Atkinson & Leach 1978;Smith 1978).…”
mentioning
confidence: 99%